Cost and Time Analysis Using The Earned Value Method In The Construction of Villa Kandya House, Ubud, Bali - Febri Cahyono; Budi Witjaksana; Jaka Purnama (Journal of Social Research, 2025)
In the Kandya House Villa Construction project in Ubud, Bali, there was a delay with a time deviation of -11.97%. This delay has the potential to cause the completion time of the work, which according to the contract is scheduled for 53 weeks, to be exceeded. To evaluate the time and cost performance in this project, the Earned Value method was used. This method utilizes three main indicators, namely Actual Cost of Work Performed (ACWP), Budgeted Cost of Work Performed (BCWP), and Budgeted Cost of Work Scheduled (BCWS). The results of the analysis show that the project time performance has decreased, characterized by a Schedule Variance (SV) value of -Rp 375,265,411.62. This value reflects a significant difference between planned and completed work. In addition, the Schedule Performance Index (SPI) was recorded at 0.772, which means that time efficiency only reached 77.2% of the planned schedule. As a result, the projected completion of work using the Estimate to Schedule (ETS) and Estimate at Schedule (EAS) indicators increased to 421 days or equivalent to 60.090 weeks, far exceeding the contract duration. In terms of cost, the analysis shows suboptimal performance, with a Cost Variance (CV) value of -Rp 48,700,590.06. This indicates that the actual costs incurred were higher than the planned budget for the completed work. In addition, the Cost Performance Index (CPI) value was recorded at 0.963, which means that the efficiency of budget utilization only reached 96.3%.